Myricitrin inhibited ferritinophagy-mediated ferroptosis in cisplatin-induced human renal tubular epithelial cell injury - Lin, Jiawen; Zhang, Yangyang; Guan, Hui; Li, Shuping; Sui, Yuan; Hong, Ling; Zheng, Zhihua; Huang, Mingcheng (Frontiers in Pharmacology, 2024)
Cisplatin-induced acute kidney injury (AKI) increases the patient mortality dramatically and results in an unfavorable prognosis. A strong correlation between AKI and ferroptosis, which is a notable type of programmed cell death, was found in recent studies. Myricitrin is a natural flavonoid compound with diverse pharmacological properties. To investigate the protective effect of myricitrin against cisplatin induced human tubular epithelium (HK-2) cell injury and the underlying anti-ferroptic mechanism by this study. Firstly, a pharmacology network analysis was proposed to explore the myricitrin’s effect. HK-2 cells were employed for in vitro experiments. Ferroptosis was detected by cell viability, quantification of iron, malondialdehyde, glutathione, lipid peroxidation fluorescence, and glutathione peroxidase (GPX4) expression. Ferritinophagy was detected by related protein expression (NCOA4, FTH, LC3II/I, and SQSTM1). In our study, GO enrichment presented that myricitrin might be effective in eliminating ferroptosis. The phenomenon of ferroptosis regulated by ferritinophagy was observed in cisplatin-activated HK-2 cells. Meanwhile, pretreatment with myricitrin significantly rescued HK-2 cells from cell death, reduced iron overload and lipid peroxidation biomarkers, and improved GPX4 expression. In addition, myricitrin downregulated the expression of LC3II/LC3I and NCOA4 and elevated the expression of FTH and SQTM. Furthermore, myricitrin inhibited ROS production and preserved mitochondrial function with a lower percentage of green JC-1 monomers. However, the protection could be reserved by the inducer of ferritinophagy rapamycin. Mechanically, the Hub genes analysis reveals that AKT and NF-κB are indispensable mediators in the anti-ferroptic process. In conclusion, myricitrin ameliorates cisplatin induced HK-2 cells damage by attenuating ferritinophagy mediated ferroptosis.